2018
DOI: 10.1007/s00438-018-1484-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of sequence-based markers for seed protein content in pigeonpea

Abstract: Pigeonpea is an important source of dietary protein to over a billion people globally, but genetic enhancement of seed protein content (SPC) in the crop has received limited attention for a long time. Use of genomics-assisted breeding would facilitate accelerating genetic gain for SPC. However, neither genetic markers nor genes associated with this important trait have been identified in this crop. Therefore, the present study exploited whole genome re-sequencing (WGRS) data of four pigeonpea genotypes (~ 12X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 69 publications
(72 reference statements)
1
20
1
Order By: Relevance
“…The three CcLGs (CcLG02, CcLG03 and CcLG11) also contained M-QTLs with the highest PVE than M-QTLs on the other CcLGs suggesting their relative importance in harbouring genomic regions governing SPC in the pigeonpea. The localisation of the major M-QTLs on CcLG02 in three of the five populations in the present study could be supported by the detection on the same chromosome of some genes known for their functional role in seed storage protein accumulation such as NADH-GOGAT 25 , or for their location in the vicinity of QTL regions associated with variability of SPC in plants 37 . By projecting the population specific M-QTLs to the consensus genetic map, six consensus genomic regions, each comprising M-QTLs for SPC from two to four populations were generated.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The three CcLGs (CcLG02, CcLG03 and CcLG11) also contained M-QTLs with the highest PVE than M-QTLs on the other CcLGs suggesting their relative importance in harbouring genomic regions governing SPC in the pigeonpea. The localisation of the major M-QTLs on CcLG02 in three of the five populations in the present study could be supported by the detection on the same chromosome of some genes known for their functional role in seed storage protein accumulation such as NADH-GOGAT 25 , or for their location in the vicinity of QTL regions associated with variability of SPC in plants 37 . By projecting the population specific M-QTLs to the consensus genetic map, six consensus genomic regions, each comprising M-QTLs for SPC from two to four populations were generated.…”
Section: Discussionsupporting
confidence: 69%
“…Across populations, the number of E-QTLs detected also varied by trait. The pattern of contributions of M-QTLs vs E-QTLs to phenotypic variation for the studied traits seemed to be highly genetic background-dependent as has been frequently reported in other crops 62-65. In an earlier study, we reported a number of putative candidate gene-based nsSNP for SPC, some of which significantly cosegregated with the trait in an F 2 validation population, ICP 5529 × ICP 11605 25 . Similarly, Saxena et al 12 developed a CcFTL1 gene-based Indel marker whose cosegregation with the determinate GH locus Dt1 was validated in the same F 2 population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic and breeding efforts to improve the underutilized and neglected legume crops in architecture, period of maturation, yield, and nutritional contents have not recorded commiserate level of success as expected [88,89]. Traditional hybridization and other breeding techniques, though have been used for some desired intentions, are yet to translate to desired results.…”
Section: Genetic Improvement and Prospects Of Mnuglmentioning
confidence: 99%